A Philosophical Reading of Jacques Rancière through the Political Freedom of Democracy Enlightenment - Debora Silalahi, Artha; Silalahi, Suandi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
This paper explores Jacques Rancière’s philosophical perspective on democracy, focusing on how his ideas challenge conventional understandings of political freedom and democratic order. Rather than viewing democracy as a fixed system with clear rules and outcomes, Rancière presents it as an ongoing, often disruptive process rooted in the assertion of political will. Through a critical-philosophical approach, this paper examines how Rancière’s thought sheds light on the tensions between law, political participation, and individual autonomy. It argues that democracy, for Rancière, is defined not by institutional structures but by the continuous struggle over who gets to speak, act, and be recognised in the political space. This reading reveals the unresolved and fragile nature of democratic life, where freedom and order are in constant negotiation. By situating Rancière within broader debates on political theory and democratic practice, the paper highlights how his critique opens new ways of thinking about the ethical and political challenges of contemporary democracy. In doing so, it also raises questions about how democratic ideals from the past can still hold value in addressing present-day issues, even as their meanings evolve. Ultimately, the paper argues that Rancière’s view encourages a more dynamic and inclusive understanding of democracy—one that remains open to rethinking and renewal.